2022
DOI: 10.1002/chem.202201478
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Morphinan Opioids by TBADT‐Catalyzed Photochemical Functionalization at the Carbon Skeleton**

Abstract: The synthesis of new morphinan opioids by the addition of photochemically generated carbon-centered radicals to substrates containing an enone in the morphinan Cring, is described. Using tetrabutylammonium decatungstate (TBADT) as a hydrogen atom transfer photocatalyst, diverse radical donors can be used to prepare a variety of C8functionalized morphinan opioids. This work demonstrates the late-stage modification of complex, highly functionalized substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…can be effectively tuned by the nature of their charge balancing counter cations [2–4] . For example, tetrabutylammonium (TBA) salts of POMs are typically soluble in polar organic solvents and have been widely applied as photoredox catalysts for organic oxidation reactions [5] . Similarly, use of long chain alkylammonium or phosphonium cations allows preparation of POM‐based ionic liquids, [6] and use of rigid aromatic or amphiphilic cations can serve as structure‐directing agents, leading to the formation of highly ordered soft organic–inorganic “hybrid” materials [7–11] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…can be effectively tuned by the nature of their charge balancing counter cations [2–4] . For example, tetrabutylammonium (TBA) salts of POMs are typically soluble in polar organic solvents and have been widely applied as photoredox catalysts for organic oxidation reactions [5] . Similarly, use of long chain alkylammonium or phosphonium cations allows preparation of POM‐based ionic liquids, [6] and use of rigid aromatic or amphiphilic cations can serve as structure‐directing agents, leading to the formation of highly ordered soft organic–inorganic “hybrid” materials [7–11] .…”
Section: Methodsmentioning
confidence: 99%
“…[ 2 , 3 , 4 ] For example, tetrabutylammonium (TBA) salts of POMs are typically soluble in polar organic solvents and have been widely applied as photoredox catalysts for organic oxidation reactions. [5] Similarly, use of long chain alkylammonium or phosphonium cations allows preparation of POM‐based ionic liquids, [6] and use of rigid aromatic or amphiphilic cations can serve as structure‐directing agents, leading to the formation of highly ordered soft organic–inorganic “hybrid” materials. [ 7 , 8 , 9 , 10 , 11 ] Thermal treatment of such species can lead to the condensation of neighbouring POM molecules to yield extended bulk metal oxides, where nanostructuring and the resulting topography is impacted by the nature of the precursor.…”
mentioning
confidence: 99%
“…can be effectively tuned by the nature of their charge balancing counter cations [2–4] . For example, tetrabutylammonium (TBA) salts of POMs are typically soluble in polar organic solvents and have been widely applied as photoredox catalysts for organic oxidation reactions [5] . Similarly, use of long chain alkylammonium or phosphonium cations allows preparation of POM‐based ionic liquids, [6] and use of rigid aromatic or amphiphilic cations can serve as structure‐directing agents, leading to the formation of highly ordered soft organic–inorganic “hybrid” materials [7–11] .…”
Section: Methodsmentioning
confidence: 99%
“…Lam et al reported a TBADT-catalyzed 1,4-addition of carbon-centered radicals, which were photochemically generated from aldehydes or cycloalkanes, to morphinan opioids substrates with an enone in the morphinan C-ring, Scheme 28. 52 The reactions gave better yields when irradiated by purple LEDs at 390 nm; however, when the light source was switched to a UV LED lamp set at 370 nm, the yield was reduced.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 98%